Didactical Transposition within Reflective Practice of an Indonesian Mathematics Teacher Community: A Case in Proving the Pythagorean Theorem Topic - Rudi Rudi; Didi Suryadi; Rizky Rosjanuardi (Southeast Asian Mathematics Education Journal, 2022)
Didactical transposition plays a pivotal role in implementing reflective practice of a mathematics teacher community. Didactical transposition is a systematic approach to examine and enhance learning materials. Didactical transposition within reflective practice is conducted collaboratively between teacher trainers and teacher participants to produce an effective didactical design in encountering student learning obstacles. Thus, the objective of this study is to portray didactical transposition process accomplished by teacher trainers and teacher participants in the implementation of teacher reflective practice in the community. This study employed a methodological framework known didactical design research. Didactical design research in accordance with a reflective framework consists of four phases which are preparation, design/reflective planning for action, design/reflective implementation in action, and design/reflective evaluation and reflection after action. Research participants encompassed a teacher trainer, thirteen teachers, and thirty students. Data collection procedures were completed by employing observation and documentation. This study resulted in a didactical design which was obtained through a didactical transposition process performed by teacher and teacher trainer participants. The study discovered that didactical design developed collaboratively through didactical transposition within reflective practice in community was proven effective in overcoming the obstacles of student learning due to learning materials. Research findings are expected to be a model of professional learning for mathematics teachers in the community.